TAGUCHI METHOD PARAMETRIC OPTIMIZATION OF SURFACE ROUGHNESS AND MRR ON HPMMC IN CNC TURNING PHASE - S.N. Baba; Akbar. B.S (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2019)
In the machining phase, graphite in ceramic reinforced aluminum metal matrix composites improves machining efficiency. As a result of the forming of the tribological sheet, standard machining performance may increase. They need the most precise machining operations in the manufacturing fields, which result in the production of high-quality goods under ideal conditions. Composites' uses in engineering are increasingly expanding due to their unique properties, and these composites need the most detailed machining operations due to their manufacturing costs and applications. The fabrication of the hybrid particulate aluminum metal matrix composite (HPMC) in the sand casting method, as well as the findings of an experimental analysis on the Machinability properties of hybrid particulate aluminum metal matrix composite (HPMC), are presented in this article (Al-SiCp-Gr). The impact of strengthened silicon carbide and graphite particle ratios of 10 and 15 weight percentages was investigated. On the resulting surface roughness and material removal rate of workpieces, control factors of the turning process such as speed, feed rate, and depth of cut were investigated. Using the Taguchi, ANOVA, and S/N ratio techniques, the performance values were evaluated and optimized. It was discovered that increasing graphite strengthening and adding SCP to the mix improved the MRR while maintaining a strong surface finish. The pace and feed speeds of the cutting method are primarily responsible for surface roughness. The pace and DOC of the cutting operation have a significant impact on the MRR.